Clinicopathological Characteristics of Breast Carcinoma at RSUD Sayang Cianjur, West Java, 2022–2024 - Rohana Agustina; Ichfa Namia; Mila Anisa; Syasya Allyadina; Muhammad Fabian Pasya; Fadhilah Husnul Khotimah (Universitas Malahayati, 2026)
ABSTRACT Breast cancer is the most common malignancy in women and remains the leading cause of cancer-related mortality in Indonesia. As a referral hospital in West Java, RSUD Sayang Cianjur plays an essential role in the diagnosis and management of breast cancer. This study aims to describe the clinicopathological characteristics of breast carcinoma cases at RSUD Sayang Cianjur from January 2022 to December 2024. This research employed a retrospective descriptive design with total sampling using medical records and histopathological reports of patients diagnosed with breast carcinoma. Most patients were aged 55–64 years (34.0%), with tumors more frequently located in the left breast (55.9%). Mastectomy was the most common surgical procedure (83.3%), followed by excision biopsy (15.9%). Based on tumor staging, most cases were T1 (54.9%), while N1 was the most frequent lymph node stage (54.5%). The most common histopathological type was invasive carcinoma of no special type (NST), whereas lobular carcinoma accounted for 13.9% of cases. Grade 2 tumors were most prevalent (50.7%), followed by grade 3 (46.3%). Lymphovascular invasion was the most frequent invasive feature (41.0%), followed by fat invasion (25.0%), skin invasion (12.5%), lymph node invasion (7.6%), and perineural invasion (2.8%). In conclusion, breast carcinoma cases at RSUD Sayang Cianjur predominantly occurred in middle-aged to elderly women, with left-sided tumors, NST-type histopathology, and moderate to high histological grades. Keywords: Breast Cancer, Clinicopathological Characteristics, Carcinoma.